2012
DOI: 10.1515/hf-2011-0172
|View full text |Cite
|
Sign up to set email alerts
|

Tensile creep and recovery of Norway spruce influenced by temperature and moisture

Abstract: The time-dependent mechanical behaviour (TDMB) of wood is important when using the material for structural purposes. Recently, a new method for predicting the TDMB by numerical modelling was established based on the assumption that TDMB is caused by the sliding of the microfi brils past each other. In this study, the TDMB is examined via creep experiments on small specimens of Norway spruce latewood. The results of these are compared with results from numerical modelling. The experiments include results at two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 32 publications
2
28
0
Order By: Relevance
“…3 and Table 2 it can be concluded that with increasing MC, the IC at the same temperature increased consistently, which was in agreement with the results of previous studies (Tissaoui 1996;Moutee 2006;Engelund et al 2012 Fig. 4.…”
Section: Effect Of MC On Icsupporting
confidence: 92%
See 4 more Smart Citations
“…3 and Table 2 it can be concluded that with increasing MC, the IC at the same temperature increased consistently, which was in agreement with the results of previous studies (Tissaoui 1996;Moutee 2006;Engelund et al 2012 Fig. 4.…”
Section: Effect Of MC On Icsupporting
confidence: 92%
“…3. The IC of samples at six MCs increased continuously as temperature increased, which was consistent with the results of previous studies (Tissaoui 1996;Moutee 2006;Engelund and Salmén 2012). The IC of the samples with higher MCs was more affected by temperature than those at lower MCs.…”
Section: Instantaneous Compliance (Ic) Effect Of Temperature On Icsupporting
confidence: 91%
See 3 more Smart Citations